2018
DOI: 10.1016/j.semcdb.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT-dependent control of membrane remodelling during cell division

Abstract: The Endosomal Sorting Complex Required for Transport (ESCRT) proteins form an evolutionarily conserved membrane remodelling machinery. Identified originally for their role in cargo sorting and remodelling of endosomal membranes during yeast vacuolar sorting, an extensive body of work now implicates a sub-complex of this machinery (ESCRT-III), as a transplantable membrane fission machinery that is dispatched to various cellular locations to achieve a topologically unique membrane separation. Surprisingly, sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 180 publications
(326 reference statements)
0
91
0
1
Order By: Relevance
“…els of the main known abscission regulators do not display strong changes during exit from naïve pluripotency (Table S1, (17,28)), suggesting that accelerated abscission results from changes at the protein level, possibly via controlling the addressing of essential factors to the bridge. Our data suggest a role for the ESCRT-III protein CHMP4B, a key driver in the physical resolution of the bridge (for review see (38)), which is progressively recruited to the bridges after induction of pluripotency exit. Interestingly, in a recent study we identified a decrease in plasma membrane tension as a key regulator of exit from pluripotency (de Belly et al, submitted).…”
Section: Discussionmentioning
confidence: 84%
“…els of the main known abscission regulators do not display strong changes during exit from naïve pluripotency (Table S1, (17,28)), suggesting that accelerated abscission results from changes at the protein level, possibly via controlling the addressing of essential factors to the bridge. Our data suggest a role for the ESCRT-III protein CHMP4B, a key driver in the physical resolution of the bridge (for review see (38)), which is progressively recruited to the bridges after induction of pluripotency exit. Interestingly, in a recent study we identified a decrease in plasma membrane tension as a key regulator of exit from pluripotency (de Belly et al, submitted).…”
Section: Discussionmentioning
confidence: 84%
“…The ESCRT pathway mediates membrane fission reactions throughout the cell (Christ et al 2017, Frankel & Audhya 2018, Lippincott-Schwartz et al 2017, Schöneberg et al 2017, Scourfield & Martin-Serrano 2017, Stoten & Carlton 2018) (Figure 1 a ). Cytoplasmic protein complexes like the ESCRT machinery can separate a single continuous lipid bilayer into two discontinuous bilayers via one of two reciprocal orientations: one in which the opposing membranes are drawn together to create a membrane neck that encircles cytoplasm (here termed inside-out membrane fission) and another in which the membrane neck is surrounded by cytoplasm (outside-in membrane fission).…”
Section: The Escrt Pathwaymentioning
confidence: 99%
“…The ever-growing list of cellular membrane remodeling reactions performed by the ESCRT pathway has been reviewed extensively (Christ et al 2017, Lippincott-Schwartz et al 2017, Schôneberg et al 2017, Scourfield & Martin-Serrano 2017, Stoten & Carlton 2018). Here, we briefly summarize cellular ESCRT functions, highlighting how the machinery functions across a remarkable range of temporal and spatial dimensions and can mediate membrane fission in both possible orientations.…”
Section: The Escrt Pathwaymentioning
confidence: 99%
“…The Endosomal Sorting Complex Required for Transport (ESCRT-III) is an ancient conserved membrane remodeling machine. ESCRT-III employs polymer formation to catalyze inside-out membrane fission processes in a large variety of cellular processes, including budding of endosomal vesicles and enveloped viruses, cytokinesis, nuclear envelope reformation, plasma membrane and endolysosomal repair, exosome formation, neuron pruning, dendritic spine maintenance and preperoxisomal vesicle biogenesis [1][2][3][4][5][6][7][8][9][10][11][12] . Yeast ESCRT-III comprises four subunits Vps20, Snf7, Vps2 and Vps24, which polymerize in this order on endosomal membranes 13 , and is dynamically regulated by the ATPase VPS4 14 .…”
Section: Introductionmentioning
confidence: 99%